SHARIA MARKETING STRATEGIES IN ENHANCING CUSTOMER LOYALTY IN ISLAMIC BANKS - Muhammad Anang Firdaus (Study Program of Sharia Business Management , Faculty of Islamic Economics and Business, 2024)
Sharia marketing strategies play a crucial role in enhancing customer loyalty in Islamic banks. By prioritizing ethical conduct, education, personalization, digital transformation, relationship marketing, transparency, community engagement, and effective communication, Islamic banks can build and maintain a loyal customer base. As the Islamic banking sector continues to grow, these strategies will be essential for sustaining long-term success and ensuring that customers remain committed to their values-driven banking relationships. The research methodology for this study on Sharia marketing strategies in enhancing customer loyalty in Islamic banks employs a qualitative approach to gain in-depth insights into the experiences, perceptions, and attitudes of customers. Data collection will involve semi-structured interviews with key stakeholders, including customers, marketing managers, and Sharia compliance officers from various Islamic banks. This study identified several key factors that contribute to customer loyalty in Islamic banks through Sharia marketing strategies. First, ethical conduct and transparency in marketing practices are crucial in building trust with customers, who view these as major differentiators from conventional banks. Second, education and awareness about Sharia-compliant products and services enhance customer loyalty, with educational initiatives like seminars and workshops being effective in increasing customer appreciation of Islamic banking principles. Third, personalized services play a significant role in boosting customer satisfaction and loyalty, with tailored financial solutions and support from relationship managers being highly valued. Digital transformation also emerged as an essential factor, with accessible and Sharia-compliant digital banking services improving convenience and efficiency for customers.